TEACHING SPEECH ACTS AND INTONATION AS MEANS OF EXPRESSING MOTIVATION TO ACTION - Alisherova Madinabonu Murodiljon qizi,; Hasanova Dinora Sherali qizi,; Ahmedov Islom Sattorqul o'g'li,; Niyazova Dildora Furqatovna, (TADQIQOTLAR, 2025)
Abstract. This article examines the role of speech acts and intonation in the formation of communicative speech, their functions as a means of motivating students to  action.  The  pragmatic  nature  of  speech  acts,  the  importance  of  intonation  in conveying meaning and emotional tone are analyzed scientifically and theoretically. Also, effective methods of teaching these units, practical exercises, communication-oriented tasks and mechanisms for their use in the lesson process are presented. The article  concludes  with  recommendations  aimed  at  strengthening  the  pragmatic approach  to  language  teaching  and  developing  students'  active  communicative competence.